Copy number variation in VEGF gene as a biomarker of susceptibility to age-related macular degeneration - Md Bakri, Norshakimah; Ramachandran, Vasudevan; Hoo, Fan Kee; Subrayan, Visvaraja; Isa, Hazlita; Ngah, Nor Fariza; Mohamad, Nur Afiqah; Ching, Siew Mooi; Chan, Yoke Mun; Ismail, Patimah; Ismail, Fazliana; Sukiman, Erma Suryana; et al. (Elsevier, 2018)
Background: Several studies in various populations have been conducted to determine candidate genes that could contribute to age-related macular degeneration (AMD) pathogenesis. Objective: The present study was undertaken to determine the association of high temperature requirement A-1 (HTRA1), vascular endothelial growth factor (VEGF) and very-low-density receptor (VLDR) genes with wet AMD subjects in Malaysia. Methods: A total of 125 subjects with wet AMD and 120 subjects without AMD from the Malaysian population were selected for this study. Genomic DNA was extracted and copy number variations (CNVs) were determined using quantitative real-time Polymerase Chain Reaction (qPCR) and comparison between the two groups was done. The demographic characteristics were also recorded. Statistical analysis was carried out using software where a level of P < 0.05 was considered to be statistically significant. Result: Statistically significant associations of the VEGF gene were observed in mean copy differences between case and control subjects (P < 0.05). The consistency of both unadjusted and age-adjusted data at Copy Number CN gain (CN = 3 and CN = 4) suggested that VEGF could increase the risk of wet AMD disease (P < 0.05). None of CNVs of HTRA1 and VLDR genes showed associations with the wet AMD disease based on comparisons of the frequencies of mean (P > 0.05). Conclusion: Observations of an association between CNVs of VEGF gene and wet AMD have revealed that the CNVs of VEGF gene appears to be a possible contributor to wet AMD subjects in Malaysia.